Clinical problem solving: Mental confusion and hypoxaemia after scuba diving - Blatteau, Jean-Eric (Diving Hyperb Med, 2020)
INTRODUCTION: We report a case of a diving accident associating both cerebral symptoms and signs of respiratory impairment after two dives. The objective is to describe the process for obtaining the diagnosis. CASE REPORT: A 52-year-old man experienced mental confusion associated with hypoxaemia after surfacing. All decompression procedures were fully respected. The diver had a spatio-temporal disorientation accompanied by a marked tendency to fall asleep spontaneously. He had no dyspnoea and no cough, but crepitations at both lung bases were found with oxygen saturation at 80%. CONCLUSIONS: In this clinical case, cerebral magnetic resonance imaging and chest computed tomography scan helped to exclude other pathology that would have necessitated urgent transfer rather than urgent hyperbaric treatment. The imaging is particularly useful in case of cerebral and respiratory symptoms following scuba diving.